2017
DOI: 10.1016/j.jagp.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine among Older Adults: Differences between Baby Boomers and Pre-Boomers

Abstract: Objectives Compares use of complementary and alternative medicine (CAM) across age cohorts. Design Secondary analysis of data from the Collaborative Psychiatric Epidemiology Surveys. Participants Adults born in 1964 or earlier (n=11,371). Over half (61.3%) are baby boomers and fifty-three percent are female. Seventy-five percent of the sample is white, 10.2% African American, .6% black Caribbean, 9.35 Latino, and 4.1% Asian. Measurements The dependent variable is a dichotomous variable indicating use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
(37 reference statements)
3
13
0
Order By: Relevance
“…However, a recent study comparing the Baby Boomers cohort (1946)(1947)(1948)(1949)(1950)(1951)(1952)(1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962)(1963)(1964) to the pre-boomer cohort (those born prior to 1946) demonstrated that a higher proportion of Baby Boomers used CIM (27.7%) than pre-boomers (16.4%). [6] Aging is associated with chronic mental, cognitive, and physical conditions. The use of CIM offers less invasive, more cost-effective, culturally acceptable, and scalable therapies [7].…”
Section: Complementary and Integrative Medicine Use In The Usamentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study comparing the Baby Boomers cohort (1946)(1947)(1948)(1949)(1950)(1951)(1952)(1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962)(1963)(1964) to the pre-boomer cohort (those born prior to 1946) demonstrated that a higher proportion of Baby Boomers used CIM (27.7%) than pre-boomers (16.4%). [6] Aging is associated with chronic mental, cognitive, and physical conditions. The use of CIM offers less invasive, more cost-effective, culturally acceptable, and scalable therapies [7].…”
Section: Complementary and Integrative Medicine Use In The Usamentioning
confidence: 99%
“…In a joint survey conducted by the American Association of Retired People (AARP) and the NCCIH, the use of CIM was reported to be have increased rapidly, exceeding a prevalence of 53% among those aged 50 years and above [ 5 ]. Previously, studies had shown that older adults were more likely to use prayer for health and spiritual practices than younger adults, and were less likely to use other forms of CIM [ 6 ]. However, a recent study comparing the Baby Boomers cohort (1946–1964) to the pre-boomer cohort (those born prior to 1946) demonstrated that a higher proportion of Baby Boomers used CIM (27.7%) than pre-boomers (16.4%).…”
Section: Complementary and Integrative Medicine Use In The Usamentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal supplements and functional food products have gained increased interest recently due to their nutritional and health bene ts. [1][2][3]. Gundelia (G.) tournefortii is commonly known as Tumble thistle or tumbleweed, and a'kub in Arabic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are numerous studies confirming that women, middle-aged people, and those with higher education are the most frequent CAM users (Kemppainen et al, 2018; Kristoffersen, Stub, Salamonsen, Musial, & Hamberg, 2014; Reid, Steel, Wardle, Trubody, & Adams, 2016; Steel, Adams, & Sibbritt, 2017). Other studies have focused on specific patient groups, such as children (e.g., Groenewald, Beals-Erickson, Ralston-Wilson, Rabbitts, & Palermo, 2017; Italia, Wolfenstetter, & Teuner, 2014), men (Cant & Watts, 2019), and the elderly (e.g., Groden, Woodward, Chatters, & Taylor, 2017; Rayner & Bauer, 2017); or on particular disorders/health issues (e.g., Berretta et al, 2017; Family, Jordan, Blaxall, & Sengupta, 2018; Kristoffersen, Sirois, Stub, & Hansen, 2017; Loquai et al, 2017), indicating extensive use of CAM, especially to deal with pain, nausea, and chronic illness. Some of the most recurrent reasons are disappointment or frustration with conventional medicine, dissatisfaction with physician/patient communication, and concerns about adverse side-effects.…”
mentioning
confidence: 99%